(3fHPI ef GdMce hGdCeKGds - (3eUWai (B((3Ch eMeO eUWai(B) (3Hf eMeO aGVd Hf eMeO Cejf GdTfbjWj Gdbdbej, CHh GdCfhGQ, GdedbH HeGA GdYjfjf, J (B1328 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3jHOC GdehLhO efg Hbhdg c ef UObg ai ebGdg RGO ai LeGdg ef gGf Ydjg GdeGd JhLgJ Edjg GdBeGd ef LGA HeGdg Ld hef LGO HYQVg Pd NjQ GdeGd eG CNP ef GdMdGd hUQa ai GdfhGd hTQ GdeGd eG CNP ef GdMQGe hUQa ai GdBKGe s
(3BNQgG (B:s
(3CfUQ CNGdc XeGdekG Ch eXdhekG EfJXGQ GdaQL YHGOI cGf GdabjQ Cf jchf caQkG fYe UheYI GdQLd HjJg GdCYeGd HNhGJjegG s
(3HgG fXGe GdJYbjHIs
(3fSNI eQbeI hYdjgG HYV GdJUMjMGJs
(3HBNQgG ehYXI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs